2018
DOI: 10.1111/josh.12602
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Examination of Aggression and Study Skills From Middle to High School: Implications for Dropout Prevention

Abstract: The results highlight the importance of early prevention that combines academic enhancement and behavioral management for reducing school dropout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Data for this study were obtained from the Healthy Teens Longitudinal Study. In the previous study, researchers identified three trajectories of aggression based on teacher ratings collected annually from Grade 6 to 12 (Orpinas et al, 2018). A randomly-selected group of sixth graders from nine middle schools located in Northeast Georgia, USA, were invited to participate.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data for this study were obtained from the Healthy Teens Longitudinal Study. In the previous study, researchers identified three trajectories of aggression based on teacher ratings collected annually from Grade 6 to 12 (Orpinas et al, 2018). A randomly-selected group of sixth graders from nine middle schools located in Northeast Georgia, USA, were invited to participate.…”
Section: Participantsmentioning
confidence: 99%
“…e previous study used the aggression subscale of the adolescent version of the nationally normed Behavior Assessment System for Children-Teacher Rating Scales (BASC-TRS) to identify trajectories of student aggressive behavior (Orpinas et al, 2018). Aggression (14 items, alpha = 0.95) refers to the ''tendency to act in a hostile manner (either verbal or physical) that is threatening to others'' (Reynolds & Kamphaus, 1992, p. 48).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation